Fluxos de calor e dióxido de carbono entre o oceano e a atmosfera na região costeira e oceânica ao Sul do Brasil - Farias, Priscila Cavalheiro (2014)
The Southwest Atlantic Ocean is characterized, in winter, by the presence of an oceanographic front between the Brazil Current (BC) and the Brazilian Coastal Current (BCC). The BC/BCC oceanographic front generates intense thermal horizontal gradients between cold waters of the southern Brazilian continental shelf, dominated by the BCC, and the offshore warm waters, dominated by the BC. This study analyses, for the first time in the known literature, the coupling mechanisms between the ocean and the atmosphere from observational data taken simultaneously during an oceanographic research cruise in the southern Brazilian coast during 11-21 June 2014. In this field experiment, atmospheric radiosondes were launched and hydrographic stations were taken to measure the ocean s temperature and salinity. The study area was chosen based on the local thermal gradients presented by the BC/BCC front. Five oceanographic transects were performed perpendicular to the coast starting at the locality of Paranaguá (Paraná State) and ending in Chuí (Rio Grande do Sul State).The winter meteorological and oceanographic features were considered in the determination of ship s route. The installation of a micrometeorological tower at the bow of the ship allowed the realization of direct measurements of heat, momentum and CO2 fluxes. This study analyses the large scale meteorological conditions and explores the behavior of the marine atmospheric boundary layer using radiosondes data taken in situ. In the period when the data were collect, typical winter conditions were observed in the study area, like the cold front passage associated to an incursion of a post-frontal cold air mass and an extratropical cyclone formation. Meteorological and oceanographic measurements performed by the instruments installed on the ship were utilized to estimate the heat fluxes through bulk formulas method. This estimates were lately compared to the heat fluxes measured directly by the sensors installed in the of the ship s bow. Measurements were obtained using the Eddy Covariance method, broadly used in micrometeorological research. To obtain the turbulent fluxes at the ocean-atmosphere interface adjustments in the observational data are necessary due to the ship s motion. During most of the study period, the sea surface temperature was higher than the air temperature, thus generating a heat transfer from the ocean to the atmosphere. The heat fluxes were commonly positive on both sides of the BC (warm)/BCC (cold) oceanographic front. However, there was some difference on the heat fluxes magnitude between the two sides of the front with more intense heat exchange on the BC side. The present results show that the intense thermal horizontal gradients between the BC and the BCC waters that occur during winter in the southern coast of Brazil, the transient atmospheric systems and the air thermal advection have an important role on the marine atmospheric boundary layer modulation and on the heat and CO2 fluxes between the ocean and the atmosphere. Meteorological and oceanographic observations are fundamental to widen our understanding of the processes occurring at the ocean-atmosphere interface which are known to have primary importance on weather and climate forecast.